Calculation of Reinforced Concrete Beam Cross Sections According to General Method Included in EC2 - Kamiński, Krzysztof; Wydra, Małgorzata (Applied Mechanics and Materials, 2015)
The aim of this paper is to determine values of strains, while using the assumptions required in calculation of reinforced concrete beam cross sections according to general method included in EN-1992-1-1. It is related to application of the parabolic rectangular diagram of stresses in concrete. Various types of strain analysis were carried out using derived formulas and script written by K. Kamiński in MS Excel. A high sensitivity to changes of reinforcement area has been noticed while carrying out the analysis with the same assumptions as in the calculation of cross sections according to general requirements included in EC2. It has been found out, that the reason of this sensitivity is related to the applied design values in strain-stress relations. Other approach to the strain analysis has been suggested. The main assumption of this approach is related to using characteristic values of material parameters. Finally, both: the calculations of necessary reinforcement area and strain analysis assuming characteristic values of concrete compressive strength and yield strength of steel gained in satisfactory results conformity for area of reinforcement calculated in simplified and non‑simplified method according to EN-1992-1-1.